Cloud service analysis using round-robin algorithm for quality-of-service aware task placement for internet of things services - Nor Syazwani Mohd Pakhrudin; Murizah Kassim; Azlina Idris (Institute of Advanced Engineering and Science, 2023)
Round-robin (RR) is a process approach to sharing resources that requires each user to get a turn using them in an agreed order in cloud computing. It is suited for time-sharing systems since it automatically reduces the problem of priority inversion, which are low-priority tasks delayed. The time quantum is limited, and only a one-time quantum process is allowed in round-robin scheduling. The objective of this research is to improve the functionality of the current RR method for scheduling actions in the cloud by lowering the average waiting, turnaround, and response time. CloudAnalyst tool was used to enhance the RR technique by changing the parameter value in optimizing the high accuracy and low cost. The result presents the achieved overall min and max response times are 36.69 and 650.30 ms for running 300 min RR. The cost for the virtual machines (VMs) is identified from 0.5 to 3. The longer the time used, the higher the cost of the data transfer. This research is significant in improving communication and the quality of relationships within groups.